Chemo‐mechanical coupling model of solid oxide fuel cell under high‐temperature oxidation. (16th April 2020) - Chen, Yaping; Hao, Wenqian; Wang, Fenghui
Summary: Solid oxide fuel cell (SOFC), which is a generation device that converts chemical energy into electrical energy, has been regarded as a new generation device. The diffusion mechanism of metal cations and anions during the high‐temperature oxidation process of SOFC is proposed. Based on the equilibrium expression and diffusion equation, the chemo‐mechanical coupling relationship between oxide stress and thickness growth of the oxide layer is established by considering the influences of viscoplastic effect and oxide growth effect. The present theoretical result is consistent with the previous experimental results. In addition, the stress critical points corresponding to different parameters are different in initial oxidation stage. The oxide stress varies dramatically with time in the compressive stress phase, but it changes slowly in the tensile stress phase. The compressive stress that exists in the oxide layer increases with the growth coefficient ( D NiO = 1000‐15 000 m −1 ) of the oxide layer. The oxide stresses in oxide layer and electrolyte reduce with viscoplastic coefficient of the oxide layer from J NiO = 8.97 × 10 −5 Pa −1 s −1 to J NiO = 16.97 × 10 −5 Pa −1 s −1 and anode‐oxide layer thicknesses from H = 30 μm to H = 660 μm, while they increase with viscoplastic coefficient of the anode from J Ni = 3.81 × 10 −5 Pa −1 s −1 to J Ni = 12.81 × 10 −5 Pa −1 s −1 and kinetic parabolic constant from k p = 2.9 × 10 −15 m 2 s −1 to k p = 12.9 × 10 −15 m 2 s −1 in whole oxidation stage. The oxide thickness increases with kinetic parabolic constant in the whole oxidation stage and this changing trend accords with parabolic diffusion law. The oxide thickness increases with temperatures increasing. The results obtained from this study will provide the reference to the researches of the chemo‐mechanical coupling model and performance optimization of SOFC under high‐temperature oxidation. Abstract : Based on the equilibrium expression and diffusion equation, the chemo‐mechanical coupling relationship between oxide stress and thickness growth of the oxide layer is established by considering the influences of viscoplastic effect and oxide growth effect. In addition, the influences of growth coefficient, viscoplastic coefficient, kinetic parabolic constant, temperature on oxide stress, and oxide thickness are discussed.